An improved dual vector control for a doubly fed induction generator based wind turbine during asymmetrical voltage dips - Moumani, Youssef; Jabal Laafou, Abdeslam; Ait Madi, Abdessalam; Boutssaid, Rachid (Institute of Advanced Engineering and Science, 2024)
This paper introduces a robust and inhanced version of dual control approach based on sequence decomposition loops in order to limit transient over-currents and improving the wind turbine’s operation during asymmetrical voltage dips faults. Indeed, the doubly fed induction generator (DFIG), employed in wind energy conversion system (WECS) to produce electrical energy from wind, highly susceptible to voltage drops, which can cause transient overcurrents in both the stator and the rotor. Without any protection system, these over-currents might damage the DFIG and its converters. The strategy put forward in this work minimizes the consequences of voltage dips on wind system functioning, such as electromagnetic torque fluctuations and it enables wind turbines to maintain electrical connection with the grid in the occurrence of such disturbances. The carried-out results are promising and showed that the proposed control method can effectively minimise the oscillations in electromagnetic torque, reactive power and DC bus voltage during the asymmetrical voltage dip. This analysis also demonstrated its ability to limit the transient over-currents of the DFIG.